2017
DOI: 10.1016/j.celrep.2017.11.073
|View full text |Cite
|
Sign up to set email alerts
|

APache Is an AP2-Interacting Protein Involved in Synaptic Vesicle Trafficking and Neuronal Development

Abstract: Synaptic transmission is critically dependent on synaptic vesicle (SV) recycling. Although the precise mechanisms of SV retrieval are still debated, it is widely accepted that a fundamental role is played by clathrin-mediated endocytosis, a form of endocytosis that capitalizes on the clathrin/adaptor protein complex 2 (AP2) coat and several accessory factors. Here, we show that the previously uncharacterized protein KIAA1107, predicted by bioinformatics analysis to be involved in the SV cycle, is an AP2-intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…DAVID analysis ( Dennis et al, 2003 ) of the proteome found a significant enrichment for the biological processes of ‘synaptic vesicle endocytosis’ (22 proteins, p=1.7x10 −6 ) and ‘synaptic vesicle exocytosis’ (30 proteins, p=3.6x10 −9 ), among others. Eight proteins were of unknown function, not including the previously uncharacterized Kiaa1107 (APache) which was recently shown to be involved in synaptic vesicle trafficking ( Piccini et al, 2017 ). The only protein in the network strongly associated with the postsynaptic density (PSD) was Shank1, but there is recent evidence that Shank proteins have an unappreciated presynaptic function ( Wu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…DAVID analysis ( Dennis et al, 2003 ) of the proteome found a significant enrichment for the biological processes of ‘synaptic vesicle endocytosis’ (22 proteins, p=1.7x10 −6 ) and ‘synaptic vesicle exocytosis’ (30 proteins, p=3.6x10 −9 ), among others. Eight proteins were of unknown function, not including the previously uncharacterized Kiaa1107 (APache) which was recently shown to be involved in synaptic vesicle trafficking ( Piccini et al, 2017 ). The only protein in the network strongly associated with the postsynaptic density (PSD) was Shank1, but there is recent evidence that Shank proteins have an unappreciated presynaptic function ( Wu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…GAD2 encodes an enzyme that catalyzes the decarboxylation of glutamate to GABA and CO 2 55 . Interestingly, SYT1 , an integral membrane protein involved in synaptic vesicles, co-localizes with KIAA1107 , the gene differentially expressed in stem cell models and brains from MAPT p.R406W carriers and PSP brains, in neurons 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In the SV cycle, Rab proteins involved in these processes include Rab5, Rab4, Rab11 and Rab7 (Dey et al, 2017; Inoshita et al, 2017; Pavlos and Jahn, 2011). The increase in the formation of multivesicular body-like structures in the synaptic bouton, together with the accumulation of SV and lysosomal markers in the distal axons reported by De Gregorio et al (2017), suggests that Atl knock-down is related to alterations in membrane trafficking, implying possible changes in the organization and life cycle of the SV (Piccini et al, 2017). Here we determined that Atl knock-down modifies the accumulation of SV in the endosomal compartments positive for Rab11, but not for Rab4 (early recycling endosome) or Rab7 (late endosome) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%